Metazooplankton distribution across the Southern Indian Ocean with emphasis on the role of Larvaceans - Jaspers, Cornelia; Nielsen, Torkel Gissel; Carstensen, Jacob; Hopcroft, Russell R.; Møller, Eva Friis (Journal of Plankton Research, 2009)
The abundance and depth distribution of metazoans >20 μm were investigated at seven stations across the Southern Indian Ocean (SIO), October–November 2006. Copepod nauplii, copepodites and larvaceans dominated the metazooplankton community. Copepodites were most abundant within Agulhas Current and Southern Ocean waters, decreasing toward subtropical/tropical areas, whereas larvaceans showed the inverse pattern. The fraction <200 μm contained the majority of the zooplankton enumerated, including 81, 23 and 93% of the larvacean, copepodite and nauplii abundances, respectively. The relative abundance of larvaceans compared with copepodites increased from 7 to 44% from South Africa towards Australia. Peak copepodite biomass was observed off South Africa, while larvacean biomass was <1% of the copepodite biomass there, increasing to 6% in tropical waters. Both copepodite and nauplii biomass were positively correlated to total Chl a (P < 0.0001), larvacean biomass was only significantly related to temperature (P = 0.0213). Despite their low biomass, larvacean production was estimated to exceed the copepod production up to five times. It appears that the abundance and role of larvaceans in the SIO has been severely underestimated in previous studies; thus future investigations into the fate of organic matter will remain incomplete if this group is not adequately considered.